Factibilidad para el establecimiento de un centro turístico en el recinto Santa María, Manga del Cura - Pincay Rosado, Yolita Azucena (2013)
The research was conducted in the Santa Maria area of La Manga del Cura is an unbounded Ecuadorian area is located between Manabi , Guayas and Los Rios where there are resources that have not yet been exploited, one of them is tourism , had a duration of 180 days, the following objectives: Conduct a feasibility study for the establishment of a resort in the Santa Maria Campus , Manga del Cura, 2013 period , being specific : Perform a market study for the construction of a resort in Santa Maria Complex Manga Cura, define the technical aspects required to establish tourist center in the Santa Maria Campus Manga del Cura ; determine the economic and financial evaluation of investment using economic indicators to establish the resort, at the Santa Campus María de la Manga del Cura. The methodology used was scientific, the target population are 50,000 residents of the Santa Maria and surrounding industry , economically active population , according to INEC 2010 with a population growth of 1.21 % , the sample of the survey population is 388 people to determine demand, which was considered to owners of premises where recreational facilities are offered. By studying market demand suggested requirements regarding the quality of service we expect for recreation are met , the project requires a fixed investment of $ 148.132.54 , themselves requiring financing from 27 % at five years term and the difference will be from own resources. In the first year earnings are $ 300.305.00 , while the financial study shows an NPV of $ 897,135.28 , 226.87 % IRR and Benefit Cost Ratio of 1.38 % ,is a dollar recovers 0.75 cents , which demonstrates the feasibility of the project from the point of view of financial assessment and market study , this is demonstrated with the hypothesis that this type of investment company is profitable and feasible .